2013
DOI: 10.1158/1055-9965.epi-13-0036
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Function Time Trends in Long-Term Survivors of Childhood Cancer: A Longitudinal Study

Abstract: Background: Impaired glomerular function is one of the health problems affecting childhood cancer survivors (CCS). It is unclear whether glomerular function deteriorates or recovers. We investigated time trends and predictors of glomerular function in CCS.Methods: We evaluated repeated observations of estimated glomerular filtration rate (GFR) and glomerular dysfunction (GFR <90 mL/min/1.73 m

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 36 publications
3
57
1
Order By: Relevance
“…Most neuroblastoma patients typically require adjuvant chemotherapy, stem-cell treatment and abdominal radiation, all of which can impair function of the remaining kidney[11, 12]. Mulder et al reported early and persistent impaired glomerular function in childhood cancer survivors treated with ifosfamide, high doses of cisplatin and nephrectomy[13]. Thus, identifying risk of nephrectomy prior to resection will aid in planning future therapy and management.…”
Section: Discussionmentioning
confidence: 99%
“…Most neuroblastoma patients typically require adjuvant chemotherapy, stem-cell treatment and abdominal radiation, all of which can impair function of the remaining kidney[11, 12]. Mulder et al reported early and persistent impaired glomerular function in childhood cancer survivors treated with ifosfamide, high doses of cisplatin and nephrectomy[13]. Thus, identifying risk of nephrectomy prior to resection will aid in planning future therapy and management.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, from the viewpoint of renal function and long-term survival among uninephrectomized WT patients, the above statement is neither certain nor obvious. There are few long-term studies that evaluate the renal function in adult WTS , and we do not have sufficient scientific evidence that confirms the validity of this thesis (4,(32)(33)(34). Certainly, solitary kidney is a risk factor for the progression of CKD.…”
Section: Chronic Kidney Disease In Wtsmentioning
confidence: 84%
“…Signs of kidney damage may indicate the risk of deterioration of kidney function in the future. Long-term monitoring of renal function in WTS will facilitate the identification of those with treatmentrelated impairment of function.WTS are at risk of deterioration of renal function and CKD because of the following: decreased number of nephrons -after nephrectomy, nephrotoxic side effects of chemotherapy (carboplatin, cisplatin, ifosfamide, cyclophosphamide) or radiation therapy -if solitary kidney was in the field of radiation (3,4,26,27). According to Daw et al (3), the most severe reduction in GFR, measured by 99Tc-DTPA (technetium-99m-diethylenetriamine pentaacetic acid) clearance, occurs after nephrectomy.…”
Section: Chronic Kidney Disease In Wtsmentioning
confidence: 99%
See 2 more Smart Citations